Methadone Poisoning in Children: A Systematic Review and Meta-Analysis in Iran - Yasaman Allameh; Faezeh Sadat Akrami; Gholamreza Mohammadi; Nader Molavi; Masoudeh Babakhanian (Journal of Pediatrics Review, 2017)
Context: Symptoms of methadone poisoning, as one of the most dangerous types of poisoning, are very serious in children.